THE INFLUENCE OF LEARNING APPROACHES IN SOCCER LEARNING TOWARD PHYSICAL FITNESS OF SPORT SENIOR HIGH SCHOOL STUDENTS IN RIAU - Ricky Fernando; Kamarudin Kamarudin; Alfi Candra; Pratiwi Mutiq (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This study discusses the influence of tactical learning approaches in soccer learning on physical fitness of Sport Senior High School students in Riau. The purpose of this study is to determine the physical fitness that is applied through a tactical learning approach and through a technical approach in soccer learning. The method used in this study is an experimental method. The population in this study were 109 male students of Sport Senior High School in Riau. The number of samples which  30 students was divided by two cells using cluster random sampling. The study was taken for 4 months, which the number of treatments is 16 meetings with a frequency of 3 times a week. The instrument chosen by the author was a physical fitness test. The results of data analysis showed that based on the calculated value and analysis of the calculated t-value obtained, the calculated t-value obtained was greater than t-table at the confidence level α = 0.05 with df (n1 + n2-2) = 28, where t-value (1-1 / 2 @) in the distribution list, the value of t-table is 1.97. Since t-value is greater than t-table 1.761, it can be concluded: (1) The learning approach using tactical approach in soccer learning had an influence on the physical fitness of students of Sport Senior High School in Riau; 2) The learning approach using technical approach in soccer learning had an influence on physical fitness students of Sport Senior High School in Riau. (3) The learning approach using the tactical approach and the technical approach in soccer learning had the same effect on the physical fitness of Sport Senior High School students in Riau. However, the learning approach using the tactical approach gave more significant influence than the technical learning approach in soccer learning.